Supply, installation, testing & commissioning of public address (PA)& alarm system with all necessary accessories for 13 storied Brac University New campus building at holding no. Kha 224,,Merul Badda , Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Bengal Technological Corporation Ltd. to supply, installation, testing & commissioning of public address (PA)& alarm system with all necessary accessories for 13 storied Brac University New campus building project.